The Influence of Gender and Profession Interest on Teacher Career Selection - Tria, Arnindya Wahyu; Mentari, Sriyani (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2025)
The purpose of this study is to test and analyze the effect of gender and profession interest on teacher career selection based on Holland's theory. This research uses a quantitative approach by applying the ex post facto method which includes the use of statistical analysis. The data used in this study are primary data and secondary data. Based on the calculation, a sample of 93 students of the Accounting Education Study Program at State University of Malang was obtained from the total population of the 2020 and 2019 batches by applying a sampling technique, namely proportional random sampling. This research was measured using a questionnaire with multiple linear regression models and SPSS software version 25. The results of the F test calculation show that the gender variable and profession interest together (simultaneously) have a positive and significant effect on teacher career selection. The results of the t test calculation show that the gender variable and profession interest individually (partially) have a positive and significant effect on teacher career selection.